(untitled) (Global Journal of Science Frontier Research, 2018)
Fresh water fish has made a substantial contribution as food to the growing population. Fish proteins occupy an important place in human nutrition. They have high digestibility, besides biological and growth promoting value. However, indiscriminate use of pesticides in agricultural operations poses many problems to the aquatic environment and causes serious contamination. Continuous exposure of fish to these toxic chemicals is hazardous to their health and causing massive fish kills. In this investigations, Mastacembelus armatus a cauvery riverine fish was exposed to endosulfan an organochlorine pesticide widely used in agricultural areas in cauvery delta. It was found that the toxicity of this pesticide had caused a deleterious effects in the ionic regulations of the fish monovalent cations like Na+, K+ and divalent cations like Ca++and Mg++ play a significant role in the physiological functions of fishes. Prolonged exposure of the fish to the endosulfan toxicity had altered the ionic regulations and resulted to the morbidity of fish and finally lead to the mortality of the fish from the pesticide polluted water.